PENCIPTAAN BUKU REFERENSI WISATA KULINER DENGAN TEKNIK FOTOGRAFI GUNA MENGENALKAN POTENSI WISATA KOTA MOJOKERTO - Afriansyah, Rizal; Bahruddin, Muhammad; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2016)
Abstract: Mojokerto is a small town in East Java province. The city became the economy cantilever area of Surabaya along with other surrounding cities. Location of Mojokerto city is also quite strategically located on the provincial road leading to or from Surabaya. Therefore, the food processing industry thrives in Bypass road Mojokerto. Plenty of restaurants and other culinary destination that stand even to the middle of the city. To introduce this potential, then felt the need to create a culinary reference book of Mojokerto with photographic technique that can be used as a reference at the same time the introduction to the tourists who want to food traveling in Mojokerto. This book contains information about phone number, location, prices, facilities, favorite menu, until the operational hour.Â Kata Kunci: Buku Referensi, Wisata Kuliner, Food Photography, Kota Mojokerto.